2007
DOI: 10.1007/s00228-007-0308-2
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine in children and adolescents: the impact of age on its serum concentrations and on the extent of drug interactions

Abstract: Age is an important factor with respect to the pharmacokinetics and the extent of drug interactions of lamotrigine in children and adolescents. In this population, older individuals will need higher doses than younger ones in order to achieve the same serum concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 30 publications
5
21
0
Order By: Relevance
“…15,16 For topiramate, the present work demonstrates that clearance is inversely related to age, which is similar to other studies in children (,10 yrs) compared to adults (15-30 years), where clearance was 30%-60% higher. However, Reimers et al, 8 found a lower clearance in children and adolescents of 6% each year from 2 to 19 years. 14 In this study, no effects of age on pharmacokinetics were evident with lamotrigine or oxcarbazepine, but there was a large variability within the groups and too few patients in some of the subgroups for oxcarbazepine to demonstrate a significant effect.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…15,16 For topiramate, the present work demonstrates that clearance is inversely related to age, which is similar to other studies in children (,10 yrs) compared to adults (15-30 years), where clearance was 30%-60% higher. However, Reimers et al, 8 found a lower clearance in children and adolescents of 6% each year from 2 to 19 years. 14 In this study, no effects of age on pharmacokinetics were evident with lamotrigine or oxcarbazepine, but there was a large variability within the groups and too few patients in some of the subgroups for oxcarbazepine to demonstrate a significant effect.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, newer AEDs are increasingly prescribed not only for epilepsy but also for other indications, such as in psychiatry, neuropathic pain and migraine. [5][6][7][8] The purpose of this study was to compare the impact of age and comedication as factors contributing to pharmacokinetic variability between 4 newer AEDs (lamotrigine, levetiracetam, oxcarbazepine, and topiramate) prescribed to patients with refractory epilepsy. Treatment failure may have serious consequences on seizure control or lead to potentially serious adverse drug reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, we built the final model by considering the relationships and independence of the extracted factors. Because data on the CD ratio of LTG did not show a normal distribution (KolmogoroveSmirnov test, p < 0.001), logarithmic transformation was performed before the ratio was employed as an independent variable in this analysis [10]. The value of the intercept and the coefficient were determined for each factor influencing the CD ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Salem et al [16] reviewed 145 reports of drug interactions and suggested that interactions were more severe in children under 2 years old than in adults. Unfortunately, there have only been a few investigations of the pharmacokinetics of LTG in pediatric patients [1,3,6,7,10,14] and its plasma concentration profile in children less than 3 years old is unknown.…”
Section: Introductionmentioning
confidence: 98%
“…Classic liver enzyme inducers significantly increase the metabolism of lamotrigine, reducing the serum half-life from 15-35 hr to approximatley 8-20 hr (Hussein & Posner, 1997;Rambeck & Wolf, 1993). Ethinyl estradiol-containing oral contraceptives also significantly increase the clearance of lamotrigine (Reimers et al, 2007;Sabers et al, 2001;Sabers et al, 2003). Valproic acid inhibits the metabolism of lamotrigine and can increase the serum half-life to up to 60 hr (Biton, 2006;Ramsay et al, 1991).…”
Section: Lamotriginementioning
confidence: 99%